2000
DOI: 10.1001/archinte.160.1.113
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Decompensation in Patients With Cirrhosis During Infection With Influenza A

Abstract: Influenza A infection can cause hepatic decompensation and hospitalization in patients having cirrhosis or who are awaiting liver transplantation. Effective prevention with vaccination and early recognition and treatment of influenza are strongly recommended in these individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
50
0
3

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(57 citation statements)
references
References 10 publications
2
50
0
3
Order By: Relevance
“…3 The susceptibility of patients with cirrhosis to influenza may be explained by a direct hepatotoxic effect of the influenza virus, which might occur in a similar way to that described in animal models or in Reye's syndrome. The decreased immunity of patients with cirrhosis favors this explanation.…”
Section: Influenza In Patients With Liver Disease Before Liver Transpmentioning
confidence: 91%
See 1 more Smart Citation
“…3 The susceptibility of patients with cirrhosis to influenza may be explained by a direct hepatotoxic effect of the influenza virus, which might occur in a similar way to that described in animal models or in Reye's syndrome. The decreased immunity of patients with cirrhosis favors this explanation.…”
Section: Influenza In Patients With Liver Disease Before Liver Transpmentioning
confidence: 91%
“…In addition, we have recently shown that influenza virus may cause significant hepatic decompensation in patients with cirrhosis awaiting transplantation. 3 We report a case of influenza A viral pneumonia in a liver transplant recipient and discuss several basic and clinical aspects of this infection in patients with endstage liver disease, both before and after liver transplantation. Also, the current guidelines regarding the prevention and treatment of influenza are discussed.…”
mentioning
confidence: 99%
“…1 Patients with cirrhosis awaiting transplantation may develop hepatic decompensation after infection with influenza. 2 Whether influenza vaccine should be routinely administered before and after liver transplantation remains controversial because a suboptimal immune response to several vaccines has been reported in these patients. 3 …”
mentioning
confidence: 99%
“…First, alcoholism and ALD should not be clubbed together since significant liver disease develops in only 15% of all people who drink alcohol excessively [6] . So, clearly other etiologies such as genetic predisposition, hepatitis C and other viral infections, such as influenza [7][8][9] , may contribute to the development of the disease. Further, there are other liver diseases such as hepatitis B, hepatitis C, non-alcoholic fatty liver disease and acetaminophen overdose where patient behavior is an important component either in the acquisition of these diseases or in their adequate management.…”
Section: Ethical Concerns and Issuesmentioning
confidence: 99%